METHODOLOGY FOR THE DEVELOPMENT OF TECHNICAL CREATIVITY OF STUDENTS BASED ON THE STEAM APPROACH (USING THE EXAMPLE OF TEACHING PHYSICS). - Ochilova Ozoda Odilovna; Abdullaeva Shoira Isajanovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article explores the development of technical creativity in students through the integration of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach, with a focus on physics education. The methodology discussed herein involves a comprehensive analysis of existing literature, followed by the presentation of effective teaching methods, results from real-world applications, and a discussion on the implications for fostering technical creativity. The article concludes with insights into the significance of the STEAM approach in enhancing students' creative thinking and provides suggestions for future research and implementation.